2018
DOI: 10.1038/s41575-018-0064-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which gut microorganisms influence food sensitivities

Abstract: Finely tuned mechanisms enable the gastrointestinal tract to break down dietary components into nutrients without mounting, in the majority of cases, a dysregulated immune or functional host response. However, adverse reactions to food have been steadily increasing, and evidence suggests that this process is environmental. Adverse food reactions can be divided according to their underlying pathophysiology into food intolerances, when, for instance, there is deficiency of a host enzyme required to digest the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 187 publications
(200 reference statements)
2
58
0
14
Order By: Relevance
“…The role of the microbiome in gastrointestinal inflammatory and functional disorders has recently gathered great interest. 50 Here, we found that gluten plays an important role in shaping microbiota composition, which is consistent with previous studies. [51][52][53] In addition, changes in the intestinal microbiota of NOD/DQ8 mice were specific to the presence of dietary ATIs, including decreases in Lactobacillus and the Firmicutes/Bacteroidetes ratios, both of which have been described in CeD patients.…”
Section: Discussionsupporting
confidence: 93%
“…The role of the microbiome in gastrointestinal inflammatory and functional disorders has recently gathered great interest. 50 Here, we found that gluten plays an important role in shaping microbiota composition, which is consistent with previous studies. [51][52][53] In addition, changes in the intestinal microbiota of NOD/DQ8 mice were specific to the presence of dietary ATIs, including decreases in Lactobacillus and the Firmicutes/Bacteroidetes ratios, both of which have been described in CeD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Designing studies with the appropriate control group to evaluate these mechanisms as well as assessing clinical efficacy is a challenge. Mechanistic studies will also yield information on which subgroups might respond to which diet to give a more precision medicine approach to treating IBS 75 . No control group is ideal, and each has strengths and weaknesses.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas aeruginosa, an opportunistic pathogen detected in CD patients, is able to further degrade protease-generated gluten peptides in smaller fragments with immunogenic sequences and a higher ability to translocate trough the epithelial barrier and thus interact with the gut immune system. On the other hand, Lactobacillus spp., which is highly represented in healthy subjects, is able to decrease the immunogenicity of wheat peptides generated by human or bacterial digestions [67,68]. Partially digested gluten peptides constitutes a substrate for other gut bacteria, such as Rothia spp.…”
Section: Wheat Cultivars and The Microbiomementioning
confidence: 99%